Considerations on international rules for competition policy in the case of high-technology products and services - Ernst-Jürgen Horn (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1996)
Issues in high-technology development, production and trade have been a major cause for frictions in international economic relations in recent years. A future change for the better is not yet in sight, notwithstanding the accomplishments of the Uruguay Round of multilateral trade negotiations, hi order to contain or to reduce the conflict potential evidently existing in the field of international competition in high technology, it is widely held that it seems necessary to reshape the existing global framework for hightechnology competition. Taking into account the lessons from the protectionist races during the inter-war period, the conclusion is that only an adequate advance in international economic law can, at least in principle, be considered as a promising route towards any kind of problem resolution. In the case of globalizing markets and mutually integrating national economies, the question is becoming increasingly irresistible of why global economic relations should be subdued to a different set of rules than national economies - as expressed in the respective national competition laws. There is in fact every reason to treat foreign subjects always in the same manner as domestic subjects (,,national treatment in the GATT-language). This would have far-reaching consequences. And there is a for-rider for all this institutional change, namely the Government Procurement Agreement. If the disciplines embodied in the GPA were to be generalised, one would in fact end up in a more or less world-wide internal market where any economic agent of whatever country's origin would be entitled to sue against any other country's undue government behaviour in commercial policies.
Keywords: 330; Hochtechnologiesektor; Internationaler Wettbewerb; WTO-Regeln; Wettbewerbspolitik; Öffentliche Beschaffung; Welt